2019
DOI: 10.1186/s12879-019-4594-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on childhood hand, foot and mouth disease in Guangdong Province, China, 2010–2013: a multicity study

Abstract: BackgroundHand, foot and mouth disease (HFMD) is a serious infectious disease, which has become a public health problem. Previous studies have shown that temperature may influence the incidence of HFMD, but most only focus on single city and the results are highly heterogeneous. Therefore, a multicity study was conducted to explore the association between temperature and HFMD in different cities and search for modifiers that influence the heterogeneity.MethodsWe collected daily cases of childhood HFMD (aged 0–… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…From 2014 to 2020, we don’t find an association between extremely level of temperature and HFMD. The relationship between temperature and HFMD before the introduction of EV71 vaccine has been explored by many studies and they agreed that temperature changed the incidence of HFMD by affecting the survival and transmission of pathogen as well as human activities and behaviors [ 21 23 ]. A study in Guilin [ 13 ] found that an extremely low wind speed exerted certain protective effect which were consistent with our research.…”
Section: Discussionmentioning
confidence: 99%
“…From 2014 to 2020, we don’t find an association between extremely level of temperature and HFMD. The relationship between temperature and HFMD before the introduction of EV71 vaccine has been explored by many studies and they agreed that temperature changed the incidence of HFMD by affecting the survival and transmission of pathogen as well as human activities and behaviors [ 21 23 ]. A study in Guilin [ 13 ] found that an extremely low wind speed exerted certain protective effect which were consistent with our research.…”
Section: Discussionmentioning
confidence: 99%
“…The seasonality of HFMD indicates the potential role of climatic factors and demonstrates there are spatial and temporal variations of HFMD across China [ 10 ]. Several studies have reported that there is a non-linear relationship between climate factors, such as temperature and relative humidity, and the incidence of HFMD [ 11 , 12 , 13 ]. However, some studies have shown divergent conclusions, especially with respect to precipitation and wind speed.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, while HFMD is a self-limiting acute viral illness, it can sometimes be fatal and can cause serious complications such as meningitis or myocarditis (inflammation of lining of brain and heart, respectively). Further, HFMD is prevalent in Asia and is increasing in some countries with epidemic and pandemic potential [ 51 , 52 ]. The evidence for high temperature effects on these outcomes were robust as these studies had a low risk of bias due to better exposure assessment and/or statistical analyses that adjusted for confounders.…”
Section: Resultsmentioning
confidence: 99%